Fragmented and isolated: limited gene flow coupled with weak isolation by environment in the paleoendemic giant sequoia (Sequoiadendron giganteum). Issue 1 (27th December 2019) - DeSilva, Rainbow; Dodd, Richard S.
Abstract : Premise: Patterns of genetic structure across a species' range reflect the long‐term interplay between genetic drift, gene flow, and selection. Given the importance of gene flow in preventing the loss of diversity through genetic drift among spatially isolated populations, understanding the dynamics of gene flow and the factors that influence connectivity across a species' range is a major goal for conservation of genetic diversity. Here we present a detailed look at gene flow dynamics of Sequoiadendron giganteum, a paleoendemic tree species that will likely face numerous threats due to climate change. Methods: We used microsatellite markers to examine nineteen populations of S. giganteum for patterns of genetic structure and to estimate admixture and rates of gene flow between eight population pairs. Also, we used Generalized Dissimilarity Models to elucidate landscape factors that shape genetic differentiation among populations. Results: We found minimal gene flow between adjacent groves in the northern disjunct range. In most of the southern portion of the range, groves showed a signal of connectivity which degrades to isolation in the extreme south. Geographic distance was the most important predictor of genetic dissimilarity across the range, with environmental conditions related to precipitation and temperature explaining a small, but significant, portion of the genetic variance. Conclusions: Due to their isolation and unique genetic composition, northern populations of S. giganteum should be considered a high conservation priority. In this region, we suggest germplasm conservation as well as restoration planting to enhance genetic diversity.